Diversity and abundance of mites (Acari: Mesostigmata, Sarcoptiformes and Trombidiformes) on blueberry Vaccinium corymbosum (Ericaceae) in Michoacan, Mexico - Ayala-Ortega, José De Jesús; Estrada Venegas, Edith Guadalupe; Equihua-Martínez, Armando; González-Hernández, Héctor; Romero-Nápoles, Jesús; Vargas-Sandoval, Margarita (Revista Colombiana de Entomología, 2025)
In recent years, several species of mites have been reported as an important phytosanitary problem for blueberries. Mexico has become one of the main producers of this crop worldwide, but few studies have focused on the diversity of species present in blueberries in Mexico. Thus, the objective of this research was to report the diversity and abundance of mites associated with V. corymbosum cultivation in Michoacán (Mexico). Plant material was collected in 42 orchards of 18 municipalities of Michoacán. Samples were placed in plastic bags and stored under refrigeration at 4 °C. Mites were processed for mounting in semi-permanent preparations with Hoyer’s solution and identified using taxonomic keys. A total of 17 species of mite belonging to 12 genera, five families and three orders were collected. The families with the greatest abundance were Tetranychidae and Tenuipalpidae. Whereas Phytoseiidae was the most diverse with 11 species. The municipality of Peribán and the Biloxi variety were those that presented the greatest diversity and abundance. Of the identified species Oligonychus ilicis, Neoseiulus rufus, Typhlodromips jimenezi and Metaseiulus bidentatus are new records for Mexico. The phytophagous species O. ilicis and Brevipalpus yothersi must be further studied since they can become important pests for the crop. This research will be a starting point for further study of mites in blueberries in Mexico.